If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 35 = 2(x + 8) Reorder the terms: 35 + 5x = 2(x + 8) Reorder the terms: 35 + 5x = 2(8 + x) 35 + 5x = (8 * 2 + x * 2) 35 + 5x = (16 + 2x) Solving 35 + 5x = 16 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 35 + 5x + -2x = 16 + 2x + -2x Combine like terms: 5x + -2x = 3x 35 + 3x = 16 + 2x + -2x Combine like terms: 2x + -2x = 0 35 + 3x = 16 + 0 35 + 3x = 16 Add '-35' to each side of the equation. 35 + -35 + 3x = 16 + -35 Combine like terms: 35 + -35 = 0 0 + 3x = 16 + -35 3x = 16 + -35 Combine like terms: 16 + -35 = -19 3x = -19 Divide each side by '3'. x = -6.333333333 Simplifying x = -6.333333333
| 2r-6=3r | | S=187+0.225S | | 10-2z=-7z | | -f+3=-4f | | 7*3x=6x+9 | | x+1/3+x-2/6=x+6/12 | | -6j-8=-8j | | 1/4d+3/4=6 | | x+6/3+x-2/6=2x-3/12 | | 27=2-5(9-x) | | 3(t+1)=9 | | 1/2h-16=5/8h | | 8h+(-15h)+(-5)=(-19) | | 9+2x=15-3x | | 7(9+2x)=15-3x | | 4(c+2)=16 | | 4x/(x+2)=2 | | -(x)-6/2=15 | | 2j-3j+19=2 | | -12+n=1 | | x+9=5(2x+8) | | 80.75/z5 | | 7(9+-2x)=-33-7x | | x^2-7=4x-11 | | 1/9x^2-1=-3/4 | | 7(9+-2x)=3(5x-2) | | 4x+(4-x)-5=2x+3 | | 2(24-y)+2y=48 | | z=11+3(x+y)findx | | 7(9+-2x)=9(5x-2) | | 7(9+-2x)=9(7-2x) | | 8(100-k)+10k=840 |